2022
DOI: 10.3389/fpubh.2022.884349
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Nomograms Predicting the Risk and Prognosis of Pancreatic Cancer Patients With Lung Metastases: A Population-Based Study

Abstract: BackgroundPancreatic cancer (PC) is one of the most common malignant types of cancer, with the lung being the frequent distant metastatic site. Currently, no population-based studies have been done on the risk and prognosis of pancreatic cancer with lung metastases (PCLM). As a result, we intend to create two novel nomograms to predict the risk and prognosis of PCLM.MethodsPC patients were selected from the Surveillance, Epidemiology, and End Results Program (SEER) database from 2010 to 2016. A multivariable l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
(42 reference statements)
3
6
1
Order By: Relevance
“…In gastrointestinal tumors such as liver, gastric, and colorectal cancers, the risk of concomitant liver metastases was significantly associated with advanced age, pathological type, poor tumor differentiation, bone metastases, lung metastases, high TNM stage, and unsystematic treatment [ 55 , 56 , 57 ]. In this investigation, we found that the risk variables for PC patients with concomitant liver metastasis were: male, main tumor site, pathological type, grade, T2 stage, N1 stage, metastases in the lungs and bones, larger tumor, and chemotherapy, which was a similar outcome to the results of previous studies [ 25 ]. Previous research has found that radiotherapy is a risk variable for bone metastases from pancreatic cancer; however, in our study, we found that radiotherapy was actually beneficial for patients with liver metastases [ 26 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In gastrointestinal tumors such as liver, gastric, and colorectal cancers, the risk of concomitant liver metastases was significantly associated with advanced age, pathological type, poor tumor differentiation, bone metastases, lung metastases, high TNM stage, and unsystematic treatment [ 55 , 56 , 57 ]. In this investigation, we found that the risk variables for PC patients with concomitant liver metastasis were: male, main tumor site, pathological type, grade, T2 stage, N1 stage, metastases in the lungs and bones, larger tumor, and chemotherapy, which was a similar outcome to the results of previous studies [ 25 ]. Previous research has found that radiotherapy is a risk variable for bone metastases from pancreatic cancer; however, in our study, we found that radiotherapy was actually beneficial for patients with liver metastases [ 26 ].…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, clinically relevant information needs to be integrated to determine the risk factors and prognosis of liver metastasis in PC patients. Previous studies have constructed nomogram models of distant metastases in pancreatic cancer patients, including those for bone metastases and lung metastases, to predict risk factors and prognosis, respectively [ 11 , 25 , 26 ]. However, predictive models for liver metastasis in PC patients have not been adequately studied.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to previous ndings, we found that age, primary site, degree of differentiation, histological subtype, N stage, surgery, radiotherapy, lung metastasis, and bone metastasis are risk factors for PCLM (17,18). Furthermore, the prognostic factors for PCLM, including age, degree of differentiation, histological subtype, surgery, radiotherapy, chemotherapy, and lung metastases, were largely consistent with those for liver metastases of gastric cancer (19) and rectal cancer (20), bone metastases of pancreatic cancer (21), and lung metastases of PC (22). It was reported that the median survival of patients with untreated distant metastases is no more than 6 months (23) and the median survival of PCLM patients in this study was 5 months for both the SEER cohort and our cohort.…”
Section: Discussionsupporting
confidence: 54%
“…For PNET, TNM stage, a classic indicator, still has advantages for pathological staging [ 11 ]. For many cancers, the nomogram grading approach is superior to conventional staging systems and has become a new standard [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%